1999
DOI: 10.1016/s0741-5214(99)70381-2
|View full text |Cite
|
Sign up to set email alerts
|

Venous morbidity after superficial femoral-popliteal vein harvest

Abstract: SFPV harvest results in minimal mid-term to late-term lower-extremity venous morbidity despite outflow obstruction. The most likely mechanisms preserving clinical status include the low incidence of mild reflux, the presence of collateral venous channels, and the lack of progression in abnormal harvest limb physiology. The absence of the ipsilateral GSV does not adversely affect clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 21 publications
4
96
2
1
Order By: Relevance
“…Several studies have documented minimal lower extremity venous comorbidities when the vein is harvested between the deep and popliteal veins. 14,16,17 In our case, the trauma service had ligated both the IVC and bilateral iliac veins as a damage control maneuver. The patient subsequently developed early, progressive lower extremity edema.…”
Section: -511mentioning
confidence: 87%
“…Several studies have documented minimal lower extremity venous comorbidities when the vein is harvested between the deep and popliteal veins. 14,16,17 In our case, the trauma service had ligated both the IVC and bilateral iliac veins as a damage control maneuver. The patient subsequently developed early, progressive lower extremity edema.…”
Section: -511mentioning
confidence: 87%
“…Antoniou et al 5) observed a graft infection or recurrent bleeding in 44% of mid-to long-term venous morbidity after an FV harvest is minimal. 17) The major drawback to this technique is the long operation time. 11) In the present case, we prioritized a resistance to infection when choosing the graft material, as the causative organism was not identified pre-or intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Autogenous SFV grafts have already been utilized successfully in several areas of major venous reconstructions (16). From this experience, it is well known that harvesting the SFV peripherally to the profound femoral vein inflow is well tolerated and associated with only minimal lower extremity venous morbidity, even in the absence of the ipsilateral great saphenous vein (5,16). Apart from these safety aspects, its caliber is larger than that of the external iliac vein, and its length allows at least two interposition grafts to major MHV trunks to be performed using a single SFV.…”
Section: Discussionmentioning
confidence: 99%
“…An extended right lobe including venous drainage by the trunk of the middle hepatic vein (MHV) would guarantee optimal graft function (2). As donor safety represents the paramount concern, the majority of Western groups currently advocate a standard right hemihepatectomy (Couinaud's segments [5][6][7][8] in RL-LDLT, preserving the intact MHV for the donor (3). There is a heated debate about the need to preserve sizable (>5 mm in diameter) MHV tributaries during donor hepatectomy followed by vascular reconstruction using autogenous vein interposition grafts.…”
Section: Introductionmentioning
confidence: 99%